A qualitative systematic review exploring lay understanding of cancer by adults without a cancer diagnosis. (22nd December 2013) - Balmer, Claire; Griffiths, Frances; Dunn, Janet
Abstract Aim To explore the lay understanding of cancer. Background Lay understanding of illness is shaped by social identity, personal biography and experience. It informs how ill health is defined, concerns are managed and interventions evaluated. An appreciation of lay understanding is therefore vital to enable relay of effective and appropriate health information to the public and care provision and support to patients. Design A qualitative systematic review using Thomas and Harden's (2008) approach to thematic synthesis. Data sources Key social science, nursing and medical databases, cancer organization websites for grey literature and a hand search of references retrieved from particularly relevant articles and journals. Review methods Thematic synthesis of eligible papers (studies on adults without a cancer diagnosis, generated from WHO‐defined 'high‐income' countries and published between 1990–2011). Only those focusing on the understanding of cancer, rather than screening or cancer genetics, were included. Results Six analytical themes were identified from 26 papers, generated from 25 studies. Explorations of the causes of cancer and interpretation of personal risk dominated the published work. These revealed a significant complexity in lay understanding. This review has also highlighted the need for additional work, particularly in gaining an understanding of the stigma and fear that surround cancer. Conclusion The themes identified by this review have the potential to inform the development of appropriate health promotion strategies and clinical services for those living with cancer and lead to a better understanding of problematic areas, such as late presentation, which continues to impede efforts to improve cancer survival.